Assessment of the Mg–Al–Sb system supported by experiments and extrapolation to the Mg–Al–Sn–Sb quaternary system. (September 2022) - Zhang, Jiyuan; Yuan, Yuan
Abstract: The phase equilibria and transformation temperatures of the Mg–Al–Sb ternary system were investigated via thermodynamic modeling coupled with key experiments. The isothermal section of the Mg-rich corner at 400 °C and two vertical sections in the Mg–Al–Sb ternary system were constructed by the metallographic analysis and thermal analysis. No ternary compound was found in the Mg-rich corner. The thermodynamic modeling of Al–Sb and Mg–Al–Sb systems was carried out using the CALculation of PHAse Diagram (CALPHAD) approach. The associated solution model was used to describe the short-range ordering for the liquid phase. The calculated phase diagram and thermodynamic property of the Al–Sb system are consistent with most of the experimental data. A set of reliable and self-consistent thermodynamic parameters were obtained combining with Mg–Sb and Mg–Al systems as well as the updated Al–Sb system in the present work. The solidification paths in Sb-containing Mg alloys were analyzed using the present thermodynamic description of Mg–Al–Sn–Sb quaternary system extrapolated from that of the constituent sub-ternary systems. Highlights: The isothermal section and two vertical sections of the Mg–Al–Sb in rich-Mg side phase diagrams were constructed. Al–Sb and Mg–Al–Sb systems have been re-optimized using the associated model. The calculated isothermal and vertical sections agree well with experimental data. Solidification paths of AT Mg alloys were predicted by extrapolated thermodynamic description of Mg–Al–Sn–Sb system.